Scent detection dogs as a novel method for oestrus detection in an endangered species, the Tasmanian devil (Sarcophilus harrisii) - Roberts, Hannah E.; Fanson, Kerry V.; Hodgens, Naomi; Parrott, Marissa L.; Bennett, Pauleen; Jamieson, La Toya (Frontiers in Veterinary Science, 2023)
Captive breeding is a critical tool for conservation of endangered species. Identifying the correct time to pair males and females can be a major challenge for captive breeding programs, with current methods often being invasive or slow. Detection dogs may provide a non-invasive way to determine female receptivity, but this has not been explored in captive wildlife. This exploratory study investigated the use of detection dogs as a novel method of oestrus detection in the endangered This is a provisional file, not the final typeset article Tasmanian devil (Sarcophilus harrisii). Faecal samples were collected from 11 captive female devils during the breeding seasons of 2020 and 2021. Three dogs with prior detection experience were trained and subsequently assessed (n = 188 searches per dog), on their ability to discriminate between oestrus and non-oestrus devil faecal samples, in a one sample set-up. When assessed on training samples, dogs were able to correctly discriminate oestrus from non-oestrus with a mean sensitivity of 69.1% and mean specificity of 65.7%. When assessed on novel samples, their sensitivity to oestrus dropped (mean sensitivity of 48.6%). However, they were still able to correctly identify non-oestrus samples (mean specificity of 68.1%). This study is the first to explore detection dogs' ability to identify oestrus in a captive breeding program for endangered wildlife, providing a promising tool for non-invasive monitoring of reproductive status in wildlife.